Authentic Leadership in Lithuanian Healthcare: A Qualitative Exploratory Study of Health Managers’ Views and Experiences - Lazinkaitė, Miglė; Avery, Mark; Olley, Richard; Stankūnienė, Aurima; Czabanowska, Katarzyna; Stankūnas, Mindaugas (Acta medica Lituanica, 2026)
Authentic Leadership (AL) is a value-based approach to leadership that focuses on self-awareness, relational transparency, balanced processing, and an internalized moral perspective. AL nurtures a supportive, high-trust work environment that boosts team cohesion, productivity, and ethical standards. In the healthcare workforce, the challenges and demands of person-centred care are significant, making AL a valuable opportunity to enhance the effectiveness of leadership and management. This study explored the key constructs and opportunities of AL within the context of the Lithuanian health system.A qualitative interpretative phenomenological approach was used to conduct semi-structured interviews with senior healthcare managers in Lithuania. The goal was to explore how these leaders understood and practiced AL. Thematic analysis was performed on the transcriptions of study participants’ semi-structured interviews about perceptions of AL’s four theoretical dimensions.The findings identified that Lithuanian healthcare leaders view self-awareness, moral integrity, and adaptability as central to effective leadership. Leaders emphasized self-reflection, openness to feedback, and moral consistency as crucial to their roles, enabling them to manage complex ethical responsibilities and strengthen organizational trust. AL has been shown to promote resilience in dynamic healthcare settings, thereby enabling adaptability and innovation. Leaders valued transparency and inclusive decision-making to ensure that diverse perspectives informed the team strategies.This study indicates that AL is an effective leadership approach for healthcare management in Lithuania. Our findings suggest that healthcare organizations could benefit from AL-based training programs, which may improve leaders’ self-reflective practices, ethical decision-making, and collaboration skills.
Keywords: authentic leadership; healthcare; management; Lithuania